Neonatal therapeutic hypothermia outside of standard guidelines: a survey of U.S. neonatologists. (9th August 2017) - Burnsed, Jennifer; Zanelli, Santina A.
Abstract: Aim: Therapeutic hypothermia is standard of care in term infants with moderate‐to‐severe hypoxic–ischaemic encephalopathy (HIE). The goal of this survey was to explore the attitudes of U.S. neonatologists caring for infants with HIE who fall outside of current guidelines. Methods: Case‐based survey administered to members of the Section on Neonatal‐Perinatal Medicine of the American Academy of Pediatrics. Results: A total of 447 responses were analysed, a response rate of 19%. We found significant variability amongst U.S. neonatologists with regard to the use of therapeutic hypothermia for infants with HIE who fall outside standard inclusion criteria. Scenarios with the most variability included HIE in a late preterm infant and HIE following a postnatal code. Provision of therapeutic hypothermia outside of standard guidelines was not influenced by number of years in practice, neonatal intensive care type (NICU) or NICU size. Conclusion: Significant variability in practice exists when caring for infants with HIE who do not meet standard inclusion criteria, emphasizing the need for continued and rigorous research in this area.